Fusarium oxysporum assisted green synthesis of small-sized silver nanoparticles for high antibacterial, and photocatalytic decolorization performances - Reyad M. El-Sharkawy; Inas A. Ahmed; Taghrid G. Kharboush (BMC Microbiology)
Abstract Background Novel platforms using nanotechnology-based medicines have exponentially increased in our daily lives. The unique characteristics of metal oxide and noble metals nanoparticles make them suitable for different fields including antimicrobial agents, cosmetics, textiles, wound dressings, and anticancer drug carriers. Methods This study focuses on the biosynthesis of small-sized SNPs using exo-metabolites of Fusarium oxysporum via bioprocess optimization using Plackett-Burman (PBD) and central composite designs (CCD) while evaluating their multifaceted bioactivities. Results The successful biofabrication of smaller-sized SNPs with an average particle size of ~ 5 nm was achieved upon the bioprocess optimization. The developed SNPs exhibited significant antibacterial activity against multidrug-resistant bacterial pathogens in a concentration- and time-dependent manner. The minimum inhibitory concentrations (MICs) for SNPs were 0.078 µg/ml (Escherichia coli), 0.156 µg/ml (Pseudomonas aeruginosa), and 1.25 µg/ml (Enterococcus faecalis), while the minimum bactericidal concentrations (MBCs) were correspondingly 0.156 µg/ml, 0.312 µg/l, and 1.25 µg/ml. SNPs-treated cells displayed bacteriostatic and bactericidal effects as revealed by time-kill assay and the ultrastructure changes observed in SEM and TEM analyses. The results marked the potent antioxidant activity of SNPs against DPPH, O2 •−, H2O2, and OH-radicals with IC50 values of 74.3, 96.7, 116.6, and 167.9 µg/ml, respectively. Significantly, the biosynthesized SNPs displayed cytotoxic activity on MCF-7, A549, and HepG-2 cell lines with IC50 values of 89.4, 121.4, and 138.9 µg/ml, respectively. SNPs exhibited promising photocatalytic efficiency at different concentrations and times compared with dark conditions. The highest decolorization percentage of crystal violet dye was 98.60% after 240 min at 100 µg SNPs concentration. Conclusions The green synthesis of SNPs by F. oxysporum exometabolites is eco-friendly, and inexpensive, with the production of small-size, and greatly stabilized nanoparticles. This study corroborated that SNPs can be highly promising enough to be applied for antibacterial and anticancer control systems, for ameliorating free radical-related disorders, and as a photocatalyst for wastewater treatment.